Physico-chemical characterization of Annapavala Chenduram - A Siddha herbo marine formulation - N, Sabari Girija; L, Sakthimanipriya; MA, Sinekha; K, Prithiviraj; P, Shanmugapriya; R, Madhavan (International Journal of Ayurvedic Medicine, 2022)
Annapavala Chendhuram (APC) is the herbo – marine formulation in Siddha. Annabedhi (Green vitriol) is one of the Uparasam (Hydro chemicals) and Kodipavalam (Coral) is one of the Navamanigal (Nine gems). These both are the main ingredients of APC. Present day demand of Siddha formulations has been raised globally due to increased response towards Siddha system of medicine. Therefore, certain things like standardization, quality control, and safety became essential requirements for Siddha formulations. The test drug APC was prepared at Gunapadam (Pharmacology) lab of National Institute of Siddha, Chennai as per traditional method (incineration) mentioned in the classical texts. Physico‑chemical and instrumental analysis including Scanning Electron Microscopy (SEM), X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR) was performed as per PLIM (Pharmacopeia Laboratory of Indian Medicine) guidelines. The pH of test drug APC was 8.34. It contains 0.56% acid insoluble ash and Solubility in the water was 6.75%. Quantitative measures of chloride, sulphate, carbonate, iron, calcium, sodium and potassium was 0.63%, 1.21%, 11.84%, 19.56%, 14.85%, 2.2%, 3.5% respectively. Scanning Electron Microscopy analysis revealed that particle size of APC about 200nm. This study suggests that quality specifications of APC can be developed using parameters described in Siddha along with analytical tools available today.Text